Factors influencing accountability practices in managing NGOS funds: the case of Yemen - Abdullah Ahmed, Abdulwahed Hamoud; Zainol, Zaini; Mokhtar, Norsyahida (Bussecon International Academy, 2022)
This study examines the factors influencing accountability practices in funds management of local nongovernmental organizations (NGOs) in Yemen. A total of 75 local NGOs operate in Yemen, receiving local and foreign funding. A structured online questionnaire was employed for data collection. This study found that accountability was not widely practiced among the NGOs in Yemen. The level of accountability practices of these NGOs was significantly influenced by funding competition and perceived motive. The results of the study offer important implications for both policymakers and NGOs. The relevant regulatory bodies must formulate policies to enhance the NGOs’ accountability for improved efficiency and transparency. The NGOs, on the other hand, are expected to be transparent in ensuring the resources are well managed, and services are delivered efficiently and effectively to the recipients.